(untitled) (Raparin Journal of Humanities (RJH), 2024)
This study investigates one of the most significant features of the social history of Mahabad, which is one of the famous cities in Kurdistan. Inspite of that Mahabad was the capital of Republic of Kurdistan politically, it, socially, had a long social characteristic. Because Mahabad located on one of the commerce roads between East and West, it became a crucial center of commerce between East and West areas; moreover, it became a lively city socially with having its own culture and social features. Coming various people from Russia and Ottoman Empire to Mahabad for commerce and being many Jewish and Christian families in the city, certainly, had a considerable influence on the social condition generally and on the culture and social culture of the city specifically. This study includes two scientific themes. In the first theme, we talk about the protocols of hospitality, horse riding, and jokes and games in Mahabad, in which the city had its own feature in this regard. Besides, in the second theme we have dealt with three social phenomena: wedding ceremonies, parties, and visiting the cemetery of good people. The significance of the study is that only few researches have been conducted in this socio-historical domain although it is very important.